ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RISK PROFILES, GOOD CORPORATE GOVERNANCE, EARNING DAN CAPITAL PADA BANK PERKREDITAN RAKYAT (BPR) DI KOTA DENPASAR - I Made Adi Suwandana; Anak Agung Putu Gede Arie Susandya (Jurnal AKSES, 2019)
This study aims to determine the level of health of the Bank Perkreditan Rakyat (BPR) in Denpasar in terms of risk profile, good corporate governance, earnings and capital. Data analysis technique refers to Bank Indonesia Regulation Number 13/1 / PBI / 2011 concerning the Rating of Soundness of Commercial Banks, Bank Indonesia has established a risk-based Bank soundness rating system by applying RGEC (Risk Profile, Good Corporate Governance, Earning) factors , Capital) to assess the soundness of a bank. The results of the data analysis show the level of health of the Bank Perkreditan Rakyat (BPR) in Denpasar in terms of the risk profile is very healthy with a composite weight of 90 percent, indicated by the ratio of Non Performing Loans is 0.67 percent is ranked 1 is considered low, and Loan to Deposit The ratio is 118.99 percent, ranked 2nd, rated low to moderate. The level of health in terms of good corporate governance is healthy with a composite weight of 80 percent, indicated by the score of Good Corporate Governance is 1.82 is ranked 2 is considered good. The level of health in terms of earnings is very healthy with a composite weight of 100 percent, indicated by the ratio of Return On Assets is 3.83 percent is ranked 1 is considered very healthy, and the Net Interest Margin ratio is 7.58 percent is ranked 1 is considered very healthy . The level of health in terms of capital is very healthy with a composite weight of 100 percent, indicated by the value of the Capital Adequacy Ratio is 22.26% is ranked 1 is considered very good.